Serum progesterone profiles in Saanen crossbred goats during a 5-day progestin-based estrous synchronization protocol - Thom Inya (2018)
A short-term progestin-based estrous synchronization protocol was tested using a 5-day progesterone plus a luteolytic dose of prostaglandin (PG) and equine chorionic gonadotropin (eCG) in Saanen crossbred dairy goats. Synchronization was monitored by measuring serum progesterone (P4) via enzyme immunoassay. The treatment was initiated by inserting an intravaginal progesterone release device (CIDR-G) at day 0 (D0) along with intramuscular cloprostenol 125 μg, followed by 100 IU eCG on D3. The CIDR-G was removed on D5. After treatment, estrus was observed twice daily using a vasectomized buck. Blood samples were collected daily from D0 until D11 for serum P4 analysis. Eight out of nine (89%) does came into estrus with an average onset of estrus at 45.0 ± 4.4 hr (mean ± SE) after CIDR-G removal. The P4 concentration immediately before the treatment was 22.4 ± 5.3 ng.mL -1 (range 1.3 to 37.8 ng.mL -1 ). The highest concentration appeared on D1 and the lowest on D7. There was a difference between serum P4 concentrations during CIDR-G insertion (D1-D5) and after CIDR-G removal (D6-D9) (26.0 ± 2.4 and 3.4 ± 0.4 ng.mL -1 , respectively, P < 0.001). The P4 profiles implied that this protocol based on 5-day progestin-based estrous synchronization can be applied successfully to crossbred dairy goats.